Sequential pulmonary resections by uniportal video-assisted thoracic surgery for bilateral multiple pulmonary nodules - Xu, Guangwen; Wang, Gaoxiang; Mei, Xinyu; Wu, Mingsheng; Li, Tian; Xie, Mingran (Frontiers in Oncology, 2022)
Objective The aim of this study was to evaluate the effect of sequential pulmonary resections by uniportal video-assisted thoracoscopic surgery (VATS) for bilateral multiple pulmonary nodules (BMPNs). Methods A single-center, prospective, nonrandomized study was performed on patients who underwent one-stage or two-stage operations by uniportal VATS. The clinical, pathological and perioperative data were summarized and analyzed from January 2021 to December 2021. Results A total of 80 patients were included during the study period. Sequential pulmonary resection by uniportal VATS was underwent in 40 patients. There were no perioperative deaths and serious complications, 2 patients had postoperative pneumonia, 3 patients had transient atrial fibrillation, 1 patient had persistent severe air leakage, 1 patient occurred hemoptysis. The one-stage group had less operative time, surgical blood loss, pleural drainage, chest tube duration and postoperative admission duration(P<0.05). The results of pathological examination of pulmonary nodules revealed adenocarcinoma in situ (n=12), minimally invasive adenocarcinoma (n=24), invasive adenocarcinoma (n=42), squamous carcinoma (n=1),and benign nodules (n=10). The pathological diagnosis included multiple primary lung cancers (30/40, 75%), single primary lung cancer (6/40, 15%). The most advanced pathologic stage of the primary lung cancer was classified as IA (n=19), IB (n=5), II (n=3), and IIIA (n=2). Conclusion For patients with excellent pulmonary function, sequential pulmonary resection by uniportal VATS is a safe and feasible for BMPNs. Strict control of surgical indications, reasonable preoperative planning, accurate intraoperative operation, and standardized perioperative management can effectively reduce complications and maximize benefits for suitable patients.